SYRIAN REFUGEES CHILDREN CHALLENGES AND PROBLEMS OF LEARNING THE ENGLISH LANGUAGE AS A FOREIGN LANGUAGE: THE CAMPGROUND OF BARIKA AS AN ILLUSTRATION IN KURDISTAN REGION, IRAQ - Hazhar Ramadhan Ahmed (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
The aim of this study was to recognize the difficulties and obstacles of teaching EFL to children, as well as the answers to existing challenges. In a semi-structured interview with seven Children Syrian refugees and one EFL teacher, a qualitative analysis design was used. The data review findings revealed four critical obstacles for Children Syrian refugees in studying and teaching EFL in Camp of Barika in KurdistanRegion . Social, educational, economical, and structural problems are now the challenges. Childcare, shortage of essential needs, and psychiatric dangers has been the key socioeconomic problems. The failure to cover daily family costs, like food, and medication, contributed to financial difficulties. Due to a weak educational context, difficulty with the English languageis short of qualified teachers to work with Syrian refugees, and be short of inspiration, educational difficulties were primarily induced. The main educational problem is the budget problem for the demands of other learning resources, the current class climate, the lack of teachers, and the low academic history of Children Syrian refugees. This research recommends that by utilizing fewer sophisticated and learner-friendly teaching approaches, the program in EFL teaching can be conveniently configured. EFL teachers can give special concentration to the teaching of EFL to children Syrian refugees if appropriate. The organization would pay additional benefits to inspire teachers in order to offer more effort.